TEACHER’S STRATEGIES IN REDUCING STUDENTS’ DISRUPTIVE BEHAVIOR IN INDONESIAN EFL CLASSROOM - Umar Umar; Rahmat Khair (English Review: Journal of English Education, 2022)
The objectives of this research were (1) to explore kinds of students’ disruptive behaviors, (2) to find out teacher’s strategy in managing students’ disruptive behavior, (3) to explore factors causing students’ disruptive behavior and (4) to find out the impact of students’ disruptive behaviors on students’ speaking skill in SELF classroom of a senior high school. This research applied case study design in order to get more understanding about the phenomenon of students’ disruptive behaviors. In terms of participant, the researcher focused on observing the SEFL students of eleventh year at SMA Negeri 1 Tinambung, West Sulawesi. There were eleven classes and the researcher took one class purposively. Classroom observation was conducted in order to get the data about kinds of students’ disruptive behavior, teacher’s strategy in dealing with disruptive behavior, and impact of students’ disruptive behavior on students’ speaking skill. Moreover, semi-structured interview was used to get factors causing students’ disruptive behavior. There are eight kinds of disruptive behavior found in this research along with the new one namely inattention, apathy, moving about the room, annoying others, cheating, needless talk, disrupting (shouting), and exaggeration talk. In order to deal with students’ disruptive behavior, the teacher applied some strategies namely, proximity interference, touch interference, signal interference, calling out names, asking questions, request & demands, and psychological punishment. Researcher also found five factors that cause students’ disruptive behavior which were classified into three categories namely physiological factor, environmental factors, and social factors and found that that disruptive behavior impacted linguistically on students’ speaking skills that covers students’ fluency, vocabulary, accuracy, and pronunciation.